A Water‐Soluble Perylene Bisimide Cyclophane as a Molecular Probe for the Recognition of Aromatic Alkaloids. Issue 11 (31st January 2019) - Sapotta, Meike; Hofmann, Anja; Bialas, David; Würthner, Frank
Abstract: Herein, we report a water‐soluble macrocyclic host based on perylene bisimide (PBI) chromophores that recognizes natural aromatic alkaloids in aqueous media by intercalating them into its hydrophobic cavity. The host–guest binding properties of our newly designed receptor with several alkaloids were studied by UV/Vis and fluorescence titration experiments as the optical properties of the chromophoric host change significantly upon complexation of guests. Structural information on the host–guest complexes was obtained by 1D and 2D NMR spectroscopy and molecular modelling. Our studies reveal a structure–binding property relationship for a series of structurally diverse aromatic alkaloids with the new receptor and higher binding affinity for the class of harmala alkaloids. To our knowledge, this is the first example of a chromophoric macrocyclic host employed as a molecular probe for the recognition of aromatic alkaloids. Abstract : Be my guest : A water‐soluble perylene bisimide cyclophane host recognizes structurally diverse natural aromatic alkaloids by binding them in its hydrophobic cavity. Encapsulation of the guest is signalled by distinct changes in the optical properties of the host.